2022
DOI: 10.3390/jof8080869
|View full text |Cite
|
Sign up to set email alerts
|

Virulence-Associated Genes of Calonectria ilicola, Responsible for Cylindrocladium Black Rot

Abstract: The Cylindrocladium black rot caused by Calonectria ilicicola is a destructive disease affecting a broad range of crops. Herein, we study virulence-associated genes of C. ilicicolaCi14017 isolated from diseased peanut roots (Arachis hypogaea L.). Ci14017 was identified via phylogenetic analysis of the internal transcribed spacer region and standard Koch’s postulate testing. Virulence-associated genes were based on genome analyses and comparative analysis of transcriptome and proteome profiles of sensitive and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…The dual culture technique was used to screen isolates with antagonistic activity against FocTR4 14,013 strain and other pathogens, such as Alternaria alternata, Calonectria ilicicola (Chen et al, 2022), Colletotrichum gloeosporioides, F. oxysporum from Morinda officinalis (Dong et al, 2019), Helminthosporium maydis, Lasiodiplodia pseudotheobromae (Chen et al, 2020), and Stagonosporopsis pogostemonis (Luo et al, 2022). All of the strains were cultured by PDA plates at 28°C.…”
Section: Screening Of Antagonistic Isolatesmentioning
confidence: 99%
“…The dual culture technique was used to screen isolates with antagonistic activity against FocTR4 14,013 strain and other pathogens, such as Alternaria alternata, Calonectria ilicicola (Chen et al, 2022), Colletotrichum gloeosporioides, F. oxysporum from Morinda officinalis (Dong et al, 2019), Helminthosporium maydis, Lasiodiplodia pseudotheobromae (Chen et al, 2020), and Stagonosporopsis pogostemonis (Luo et al, 2022). All of the strains were cultured by PDA plates at 28°C.…”
Section: Screening Of Antagonistic Isolatesmentioning
confidence: 99%
“…The sequence showed 1930 and 1718 putative secretory proteins in F018 and Ci14017, respectively. Based on the genome information, Chen et al (2022) identified 46 virulence-associated genes in Ci14017 through a comparison of transcriptomes and proteomes between resistant and susceptible peanut cultivars. These genome information resources will greatly facilitate studies on the pathobiology of C. ilicicola and inform an effective RCR management strategy.…”
Section: The G Enome Of C Ilicicol Amentioning
confidence: 99%
“…The whole genome sequence of C . ilicicola has been decoded recently using the F018 strain isolated from diseased soybean plants (Liu et al, 2021) and the Ci14017 strain isolated from diseased peanut plants (Chen et al, 2022); the size of the whole genome comprised 66 Mb, encoding 17,308 and 18,366 hypothetical proteins, respectively. The sequence showed 1930 and 1718 putative secretory proteins in F018 and Ci14017, respectively.…”
Section: The Genome Of C Ilicicolamentioning
confidence: 99%